Assessment of Phenoloxidase Activity in Hemolymph of Pre, Inter and Post-Molting Stages - Joybell, E. Angeline Christina; Govindarajalu, Maduramozhi (International Journal of Scientific Research in Biological Sciences, 2018)
Phenoloxidase (PO) is an enzyme that vitally protects arthropods both internally and externally. PO protects arthropods internally from invasions by infectious microorganisms, and protects them externally by catalyzing the sclerotization of an animal’s newly formed or repaired exoskeleton In the present study determine the phenoloxidase activity in hemolymph of pre, inter and post molting stages. The phenoloxidase activity was highest in pre-molting followed by inter-molting and post-molting. The stability of the POs was very different depending on a number of factors such as temperatures, pH, substrate used, ionic strength, buffer system, and time of incubation. The results of the present study concluded that pre-molting stage has greater activity of phenol oxidase in hemolymph.